Impact of emerging technology innovations on healthcare transformation in developing countries - Ghaleb, E.A.B. (Institute of Electrical and Electronics Engineers Inc., 2020)
This study aims to explicate the strategical to take up to change. Employment of digitization of health technologies in health units of greater significance as digital transformation in healthcare plays an essential role in the improving the healthcare, knowledge transfer, and Performance system especially in developing countries and in pursuing of Millennium Development Goals (MDGs). This aim of this paper propose the factors of emerging technology usage that affect the healthcare transformation. In this Technological Innovations efficiently controls the records for documenting processes and transaction. The swift pace of digital transformation in health sector leaving healthcare providers no choice if they want to remain competitive. In Mobility Application (MA), cloud computing (CC), Internet of Things (IoT), Artificial Intelligence (AI), Big Data (BD). It is important for those who have to use the technology to accept it and to develop a better understanding of what factors lead to successful impact of these systems to improve implementation method. Essential to the quality of care and health of the society. Thus, these rationales exert that currently today providers of healthcare are embracing digital transformation in healthcare units. The benefits of digital transformation in health units are extremely compelling. They include a reduction in costs associated with employee travelling; reduction in time spent away from the patients and reduced information system (IS) in healthcare sector times. Â© 2020 IEEE.